Template matching methods for robot navigation assistance - Rodríguez Cuevas, Marisol; Díaz Ramírez, Víctor H.; Juárez-Salazar, Rigoberto; Picos, Kenia (My University, 2019)
Template matching is an effective method for object recognition because it provides high accuracy in location estimation of targets and robustness to the presence of scene noise. These features are useful for vision-based robot navigation assistance where reliable detection and location of scene objects is essential. In this work, the use of advanced template matched filters applied for robot navigation assistance is presented. Several filters are constructed by the optimization of objective performance criteria. These filters are exhaustively evaluated in synthetic and experimental scenes, in terms of efficiency of target detection, the accuracy of a target location, and processing time.
Scopus
Keywords: Robot navigation; Assistance; Sistemas